Hijacking hypermedia and other highways to learn computer science on a distancelearning course - Tina Wilson; Denise Whitelock (Association for Learning Technology, 1997)
A teaching project using Computer-Mediated Communication (CMQ to aid students' understanding of computer science took place from February to November 1995 at the Open University. The project fell within that of STILE (Students' and Teachers' Integrated Learning Environment), and the course was M205 - STILE: Fundamentals of Computing. Four different institutions were involved: the Universities of Leicester, Loughborough, De Montfort and the Open University (Ruggles, 1995; Ruggles et al, 1995; Underwood et al, 1996; Zhao et al, 1996). One of the main aims of the Open University implementation was to improve the presentation of the computer science course by enabling structured access to online facilities for both tutor-to-student and student-to-student communication. The nine tutors and 110 computer science students were situated nationwide and in Europe. In line with our partners, we used the Netscape browser version 1 revision N, with Trumpet version 2 revision B. Although use of the Web for teaching and learning was underpinned by a wealth of literature about hypertext and hypermedia (see Nielsen 1993; Laurillard, 1994), it did not successfully sustain conferencing in 1995. Therefore we also adopted the FirstClass conferencing system (version 2.6) to accommodate our distance-learning students.